2019
DOI: 10.1016/j.engstruct.2019.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Structural behaviour of stainless steel beam-to-tubular column joints

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Similar observations were made in studies investigating the behaviour of stainless steel moment resisting connections [20,21], as well as stainless steel blind-bolted connections [22]. It was found that the design provisions of EN 1993-1-8 [1], which specify design rules for carbon joints, that are also applicable for stainless steel joints [23], are adequate for stiffness predictions but overly conservative for strength predictions [20][21][22]. Wang et al [24], Bu et al [25], Song et al [26] and Gao et al [27] conducted experimental and numerical studies on the behaviour of stainless steel connections and reached similar conclusions.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar observations were made in studies investigating the behaviour of stainless steel moment resisting connections [20,21], as well as stainless steel blind-bolted connections [22]. It was found that the design provisions of EN 1993-1-8 [1], which specify design rules for carbon joints, that are also applicable for stainless steel joints [23], are adequate for stiffness predictions but overly conservative for strength predictions [20][21][22]. Wang et al [24], Bu et al [25], Song et al [26] and Gao et al [27] conducted experimental and numerical studies on the behaviour of stainless steel connections and reached similar conclusions.…”
Section: Introductionsupporting
confidence: 78%
“…It was concluded that the existing design methodology defined in EN 1993-1-8 [1] provides overly conservative strength estimations for stainless steel bolted T-stub connections [19]. Similar observations were made in studies investigating the behaviour of stainless steel moment resisting connections [20,21], as well as stainless steel blind-bolted connections [22]. It was found that the design provisions of EN 1993-1-8 [1], which specify design rules for carbon joints, that are also applicable for stainless steel joints [23], are adequate for stiffness predictions but overly conservative for strength predictions [20][21][22].…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, they developed validated numerical models and accurate design expressions for stainless steel T-stubs made of austenitic and duplex stainless steels. Meanwhile, Elflah et al [22][23][24] reported the first experimental and numerical studies on stainless steel beam-to-column bolted connections subjected to static monotonic loads. Hasan et al [25], Wang et al [26] and Gao et al [27] also performed static loading tests on stainless steel beam-to-column joints.…”
Section: Introductionmentioning
confidence: 99%
“…Elflah et al [21,22], have examined the behaviour of stainless steel moment resisting connections as well as stainless steel blind-bolted connections [23] with experimental and numerical studies. It was reported that the design provisions of EN 1993-1-8 [1], which specify design rules for carbon joints, that are also applicable for stainless steel joints [24], can predict the stiffness of the joints sufficiently accurate predictions but provides significantly conservative predictions for the strength [21][22][23]. Moreover, the structural behaviour of the moment resisting connections was investigated by three-dimensional FE model and the stiffness and resistance predictions were reported comprehensively, and proposed model validated using the experimental results [22].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the existing design rules defined in EN 1993-1-8 [1] provides overly conservative strength predictions for stainless steel bolted T-stubs [19]. Elflah et al [21,22], have examined the behaviour of stainless steel moment resisting connections as well as stainless steel blind-bolted connections [23] with experimental and numerical studies. It was reported that the design provisions of EN 1993-1-8 [1], which specify design rules for carbon joints, that are also applicable for stainless steel joints [24], can predict the stiffness of the joints sufficiently accurate predictions but provides significantly conservative predictions for the strength [21][22][23].…”
Section: Introductionmentioning
confidence: 99%